Mainstreaming ESD into Science Teacher Education Courses: A Case for ESD Pedagogical Content Knowledge and Learning as Connection - Overson Shumba; Royda Kampamba (Environmental Association of Southern Africa, 2013)
In this case study, researchers evaluated national education policies in Zambia, analysed a localised science (Chemistry 5070) syllabus, assessed a university teaching methods course, and evaluated 54 mathematics and science education students' perceptions on mainstreaming education for sustainable development (ESD) into their courses. ESD was a salient matter in education policies and in the preamble to Chemistry 5070, but not in the university teaching methods course. The chemistry syllabus included ESD issues in the 'notes' section, but was lacking in guidance on teaching and learning approaches to integrate the issues. The university Teaching Methods course did not include content and methods to assist teachers to effectively teach Chemistry 5070 and to integrate ESD issues into it. Students surveyed had some awareness of ESD issues and most were inclined to suggest that ESD issues must be mainstreamed into their courses, especially in educational theory courses; few students suggested natural sciences as carrier subjects for ESD. The findings pointed to a discrepancy among educational policies, school Chemistry 5070 and the university teaching methods courses. A paradigm shift is recommended in order that the quality and relevance of science education be viewed via the metaphor of 'learning as connection' and that Shulman's (1986) pedagogical content knowledge model be adapted so that content and pedagogy of science courses are inclusive of social and humanistic issues such as those advocated in ESD discourse.